Analisis faktor-faktor yang mempengaruhi penyerapan tenaga kerja di Provinsi Riau - Wijaya, Andi; Indrawati, Toti; Pailis, Eka Armas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research was conducted in Riau Province, aims to look at theinfluence of foreign investment, economic growth, the provincial minimum wage, and the average length of the school either simultaneously or partially to labor absorption in Riau province. Economic growth is always directed to improve the lives and well-being of society. Expansion of labor absorption needed to keep pace with the growth of young people who enter the labor market. The imbalance between labor force growth and job creation will lead to high unemployment. This research uses secondary data types. The method of analysis used in this research is descriptive quantitative method, as a simultaneously and partially analysis (multiple linear regression analysis using SPSS version 18.0). The results of the testing that has been done, simultaneous regression (F test) showed that all the independent variables have a significant effect on the dependent variable. The results of the partial regression test (t test) showed that only variable Average Length of School who have a significant effect on labor absorption in Riau province. While the variable Foreign Investment, Economic Growth and Provincial Minimum Wage has no significant effect on labor absorption in Riau province. The magnitude of the effect caused by the four independent variables together on the dependent variable was 82,9%, while the remaining 17,1% is influenced by other variables not examined in this research.Keywords : Foreign Investment, Economic Growth, The Provincial MinimumWage, Average Length of The School, and Labor Absorption